Energy consumption and pollution control from the perspective of industrial economic activity: An empirical study of China’s coastal provinces - Lu, Qing (Frontiers in Environmental Science, 2022)
From the perspective of production performance, energy supply are the basic material conditions. However, greenhouse gas, air pollution and waste water are also produced in the process of production. If the undesired characteristics are ignored in the process of performance evaluation, the production efficiency will be misestimated. Based on this, this study uses Data Envelopment Analysis (DEA) to evaluate the undesired output, and discusses the production efficiency with thermal consumption in Chinese port cities, especially with severe shipping emissions, during 2015–2019. The empirical results show that the efficiency declines first (2015–2017) and then increases (2018–2019) when considering the undesired output of wastewater and SO2 generated by thermal consumption.